Desafios tributários decorrentes do ingresso do Brasil na OCDE: Lucros no exterior, preços de transferência, subcapitalizaç\~ao e divulgaç\~ao obrigatória de planejamentos tributários - Alexandre Evaristo Pinto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The main objective of this work is to assess the challenges to be faced by Brazil to become a full member of the Organisation for Economic Co-operation and Development (OECD) in terms of tax rules related to controlled foreign companies, transfer pricing, thin capitalization, and mandatory disclosure. In this sense, a historical analysis of the OECD rules is carried out, highlighting their main characteristics. A historical analysis of the Brazilian rules is also carried out, demonstrating their main features. The conclusions point to incompatibilities between the Brazilian model and the OECD model.
Keywords: F3; F38; H2; H26; 330; controlled foreign companies; transfer pricing; thin capitalization; mandatory disclosure; tax planning; OECD